Developing Digital Scrapbook Media to Enhance Narrative Reading Comprehension in Grade III Elementary Students - Nur Faizah Salsabila; Bagas Kurnianto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading comprehension is a foundational skill for elementary students, particularly in learning short story texts where learners must grasp content, structure, and moral messages. However, low reading interest and limited engaging learning media often hinder students’ comprehension development. This study aimed to develop a Digital Scrapbook as an interactive, visual learning medium to enhance Grade III students’ narrative reading comprehension. This research employed a Research and Development (RD) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The media was designed based on constructivist principles to support active knowledge construction through the integration of text and visuals. Feasibility was examined through expert validation, and effectiveness was measured using pretest–posttest learning outcomes analyzed with the normalized gain (N-Gain). Expert validation indicated that the developed Digital Scrapbook was highly feasible, achieving an overall average feasibility score of 90.2%. Effectiveness testing showed a meaningful improvement in students’ reading comprehension performance, with an N-Gain of 0.78, indicating a high level of learning gain. The findings suggest that Digital Scrapbook media can effectively support literacy learning by increasing students’ engagement and facilitating comprehension through interactive and visually supported narrative texts. This media is therefore relevant for strengthening reading comprehension instruction in primary schools.